2013
DOI: 10.1371/journal.pone.0053806
|View full text |Cite
|
Sign up to set email alerts
|

CDC42 Is Required for Tissue Lamination and Cell Survival in the Mouse Retina

Abstract: The small GTPase CDC42 has pleiotropic functions during development and in the adult. These functions include intra- as well as intercellular tasks such as organization of the cytoskeleton and, at least in epithelial cells, formation of adherens junctions. To investigate CDC42 in the neuronal retina, we generated retina-specific Cdc42-knockdown mice (Cdc42-KD) and analyzed the ensuing consequences for the developing and postnatal retina. Lack of CDC42 affected organization of the developing retina as early as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
1
14
0
1
Order By: Relevance
“…Static cultures, in particular, gave rise to very few organoids in the absence of ROCK inhibitor. Not only does ROCK inhibition promote the survival of human pluripotent stem cells upon dissociation , the effects of ROCK inhibition on the actin cytoskeleton and the role of the cytoskeleton in the process of tissue self‐organization has also been documented , and could be a reason for the enhanced retinal formation in our experiments. Lamas et al found that ROCK i enhanced the proliferation of motor neuron progenitors derived from hESCs and hiPSCs, meaning that the effect of ROCK i in neural cultures acts not only to prevent cell death following cellular dissociation, but may also act to promote the expansion of the neural population .…”
Section: Discussionmentioning
confidence: 68%
“…Static cultures, in particular, gave rise to very few organoids in the absence of ROCK inhibitor. Not only does ROCK inhibition promote the survival of human pluripotent stem cells upon dissociation , the effects of ROCK inhibition on the actin cytoskeleton and the role of the cytoskeleton in the process of tissue self‐organization has also been documented , and could be a reason for the enhanced retinal formation in our experiments. Lamas et al found that ROCK i enhanced the proliferation of motor neuron progenitors derived from hESCs and hiPSCs, meaning that the effect of ROCK i in neural cultures acts not only to prevent cell death following cellular dissociation, but may also act to promote the expansion of the neural population .…”
Section: Discussionmentioning
confidence: 68%
“…18 Briefly, mice were darkadapted overnight, pupils were dilated with cyclogyl 1% (Alcon Pharmaceuticals, Fribourg, Switzerland) and phenylephrine 5% (Bausch & Lomb Swiss AG, Zug, Switzerland) in dim red light. Mice were subcutaneously anesthetized with ketamine (85 mg/kg; Parke-Davis, Berlin, Germany) and xylazine (4 mg/kg Bayer AG, Leverkusen, Germany).…”
Section: Electroretinographymentioning
confidence: 99%
“…For example, knockout of Cdc42 (Chen et al, ) or Rac1 (Sugihara et al, ) in mice results in severe pleiotropic defects and early embryonic lethality. Analysis of Rho GTPase activity and function in vivo therefore requires experimental approaches that allow modulation of activity in specific tissues or cell populations, and at specific time points (Chew et al, ; Govek et al, ; Heasman and Ridley, ; Heynen et al, ; Jackson et al, ; Luo et al, ; Ruchhoeft and Ohnuma, ; Wong and Faulkner‐Jones, ; Xiang and Vanhoutte, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, knockout of Cdc42 (Chen et al, 2000) or Rac1 (Sugihara et al, 1998) in mice results in severe pleiotropic defects and early embryonic lethality. Analysis of Rho GTPase activity and function in vivo therefore requires experimental approaches that allow modulation of activity in specific tissues or cell populations, and at specific time points (Chew et al, 2014;Govek et al, 2005;Heasman and Ridley, 2008;Heynen et al, 2013;Jackson et al, 2011;Luo et al, 1996;Ruchhoeft and Ohnuma, 1999;Wong and Faulkner-Jones, 2000;Xiang and Vanhoutte, 2011 Zebrafish provide an excellent model for investigation of the molecular function of vertebrate Rho GTPases in vivo (Kardash et al, 2010;Lai et al, 2005;Salas-Vidal et al, 2005;Zhu et al, 2006). Previous studies of Rho GTPase function in developing zebrafish employed microinjection of mRNA to drive global overexpression of wild-type, constitutively active, or dominant negative versions (Hsu et al, 2012;Xu et al, 2014;Yeh et al, 2011;Zhu et al, 2008, Zhu et al, 2006, or morpholino oligos for transient disruption of Rho GTPase expression (Hsu et al, 2012;Srinivas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%